2020
DOI: 10.2174/1568026620666200422105156
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Promise of Immunotherapy for Alzheimer’s Disease: A New Hope for the Development of Alzheimer’s Vaccine

Abstract: Background: Alzheimer's disease (AD) is a chronic neurodegenerative disorder and the characteristics of this devastating disorder include the progressive and disabling deficits in the cognitive functions including reasoning, attention, judgment, comprehension, memory, and language. Objective: In this article, we have focused on the recent progress that has been achieved in the development of an effective AD vaccine. Summary: Currently, available treatment options of AD are limited to deliver short-term sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 205 publications
0
11
0
Order By: Relevance
“…Amyloid beta-peptide (A β ) is obtained via the proteolytic processing of APP by β - and γ -secretases [ 226 ]. Published research demonstrated that immunization against A β has a neuroprotective effect and lessens memory deficits in transgenic mice without lowering the load of A β plaques [ 227 , 228 ]. These findings show that A β in plaques may not cause synapse degradation, and that other types of A β play a significant role in neurotoxicity in AD brains [ 229 ].…”
Section: Therapeutic Targets For Admentioning
confidence: 99%
See 1 more Smart Citation
“…Amyloid beta-peptide (A β ) is obtained via the proteolytic processing of APP by β - and γ -secretases [ 226 ]. Published research demonstrated that immunization against A β has a neuroprotective effect and lessens memory deficits in transgenic mice without lowering the load of A β plaques [ 227 , 228 ]. These findings show that A β in plaques may not cause synapse degradation, and that other types of A β play a significant role in neurotoxicity in AD brains [ 229 ].…”
Section: Therapeutic Targets For Admentioning
confidence: 99%
“…Pathologic tau in AD is hyperphosphorylated and abnormally cleaved [ 239 ]. Accordingly, inhibition of abnormal hyperphosphorylation of tau offers a promising therapeutic target for AD and related tauopathies [ 228 ]. Recent studies have linked early modifications in the structures of soluble tau proteins, particularly their phosphorylation, to neurodegeneration [ 240 , 241 ].…”
Section: Therapeutic Targets For Admentioning
confidence: 99%
“…However, there is a growing understanding regarding AD complexity, its diverse pathogenetic modes, and the dynamic interaction between the constituents that contribute to AD [ 47 ]. Furthermore, promising findings obtained from vaccination trials in transgenic animal models have encouraged the development of immunotherapeutic agents for AD treatment [ 48 ]. Various monoclonal and polyclonal antibodies have been developed against Aβ and are currently in clinical trials.…”
Section: Current Alzheimer’s Drug Therapymentioning
confidence: 99%
“…Active immunotherapies have been developed to activate an immune response in the human body of specific antibodies against Aβ [226]. Furthermore, active immunotherapies might be utilized to mediate anti-Aβ antibody responses in individuals with early stages of AD.…”
Section: Active Immunizationmentioning
confidence: 99%